Development of an artificial insemination protocol in llamas using cooled semen - Giuliano, Susana María (2012)
The objective of this study was to design an AI protocol using cooled semen to obtain pregnancies in the llama. Each raw ejaculate was subdivided into four aliquots which were extended 1:1 with: (1) 11% lactose-egg yolk (L-EY), (2) Tris-citrate-fructose-egg yolk (T-F-EY), (3) PBS-llama serum (S-PBS) and (4) skim milk-glucose (K). Each sample reached 5°C in 2.5h and remained at that temperature during 24h. Percentages of the semen variables (motility, live spermatozoa) in ejaculates and samples cooled with L-EY were significantly greater than those obtained when cooling with the other extenders; therefore this extender was used (1:1) for all inseminations. Females were randomly divided into four groups (A-D) according to insemination protocol. Group A: females were inseminated with a fixed dose of 12×10 6 live spermatozoa kept at 37°C. Group B: females were inseminated with a fixed dose of 12×10 6 live spermatozoa, cooled to 5°C and kept for 24h. Group C: females were inseminated with the whole ejaculate (variable doses), cooled to 5°C and kept for 24h. These groups (A-C) were inseminated between 22 and 24h after induction of ovulation. Group D: females were inseminated with the whole ejaculate (variable doses), cooled to 5°C, kept for 24h and AI was carried out within 2h after ovulation. Pregnancy rates were 75%, 0%, 0% and 23% for groups A, B, C and D respectively. These results indicate that it is possible to obtain llama pregnancies with AI using cooled semen and that the success of the technique would depend on the proximity to ovulation.